COMPARATIVE PRICING STRATEGY WITH COST PLUS PRICING METHOD AND ITS IMPACT ON THE PROFIT OF J’SQUARES BREWED GINGER POWDER - Sawitania Christiany Dwi Utami Boru Situmorang; Dwi Arkani Izzati; Fajar Ramadhan Akbar; Wahyu Hidayat; Muhammad Hanifudin Zakiyaa (Journal of Agri Socio Economics and Business, 2022)
The Coronavirus Disease (Covid-19) pandemic is still becoming a very difficult period for all affected countries thus far because of its multi-sector negative impact on life. Moyu Store Purwokerto is one of the MSMEs assisted by the Faculty of Agriculture, Universitas Jenderal Soedirman under the tutelage of the Tunas Bima program which is engaged in digital marketing with one of its products, the J'Square brewed ginger powder drink. At the beginning of its operation, Moyu Store Purwokerto had difficulty determining its product’s selling price. Price is one of the most important components of the marketing mix in determining the success of a marketing strategy as a newcomer. Therefore, this study aims to: (1) Calculate the selling price per unit of J'Square brewed ginger powder drink products, (2) Calculate the cost of production of the J'Square brewed ginger powder drink, (3) Analyzing the effect of the selling price of the J'Square brewed ginger powder drink and the actual selling price of the product on the profit of Moyu Store Purwokerto. The research was conducted using a quantitative descriptive method. The results of the analysis show that the value of HPP and selling price in the calculation using the full costing approach gives a higher value than variable costing. However, the actual selling price is below the resulting variation in the selling price calculation.